RELEVANCE OF USING EXPOSITORY LEARNING STRATEGIES IN TEACHING AND LEARNING ACTIVITIES IN SCHOOLS - Hasan, Angeline Kurnia; Athila, Maichel; Bertuanda, Margareta; Sapriya, Sapriya; Wilodati, Wilodati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
Education provides provisions for navigating life, with education as its main foundation. Interaction between teachers and students is very important in the learning process to create effective communication. Learning strategies are efforts made in learning to achieve goals effectively and efficiently. Learning strategies are increasingly diverse and innovative along with the development of science and technology. One of the learning strategies used is the expository learning strategy, which focuses on the delivery of material verbally from the teacher to students to ensure comprehensive understanding and achievement of the expected learning objectives. This study uses a qualitative method, where researchers conduct descriptive analysis. The descriptive analysis method is carried out by the process of pouring out explanations and descriptions as clearly as possible in an integrated, critical, objective and analytical manner about